(untitled) (Research, Society and Development, 2022)
Objective: The aim of this study was to present a case report of a surgical extraction associated with osteotomy of lower left third molar extraction erupted with extensive carious lesion, exposing its indications, surgical techniques and procedures performed. Methodology: considering the ethical aspects, and for clarifications about risks of the procedure, the patient signed the Informed Consent Form, allowing to share his image for the proper purpose. Case report: Patient F.D, 35 years old, male, ASA I, leukoderma, normosistemic, smoker, came to the dental clinic reporting “Lateral pain in his tooth”. After clinical and radiographic examination, the indication was to perform an extraction of the dental element associated with osteotomy. After extraction, irrigation of the site with 0.9% saline solution was performed in order to stimulate clot formation and favor the process of alveolus repair and tissue healing. Then, a suture was performed in place. After 7 days, the patient returned to the clinic for suture removal and monitoring of tissue repair progress. Final considerations: it is possible to conclude that from the correct evaluation and planning of the case, it is possible to obtain a satisfactory result, restoring function and health, these are some of the fundamental factors for the postoperative period to be free of complications. Considering that the extraction of third molars is a surgery often performed in offices, it is extremely important that the professional is properly qualified to perform it.